Pakistan : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
The demand pressures associated with the large terms-of-trade gains are reflected in a fast real appreciation of the ruble, although more of this has come through nominal appreciation during the last year. The risks to the outlook are evenly balanced and depend mostly on oil price developments. Current policies raise medium-term risks. IMF staff welcomed the greater focus on inflation control, but cautioned that additional exchange rate flexibility would be needed to meet the end-2006 target, especially at a time when demand pressures are exacerbated by fiscal relaxation.